SIX SIGMA : SUATU TEROBOSAN DARI SISTEM MANAJEMEN KUALITAS - Paulina Permatasari (Bina Ekonomi, 2004)
Within the last several years, Six Sigma has exploded onto the American scene as a prominent method of improving the effectiveness and efficiency of businesses. Companies like General Electric, Allied Signal, and others have saved literally billions of dollars that have resulted in increased profitability. Six Sigma is a management philosophy that attempts to improve customer satisfaction to near perfection. A six sigma company has little more than three bad customer experiences for every million opportunities. This level of near perfect performance is a significant distance from where most organizations are today. It is estimated that most companies are at the two to three sigma performance level.